Hyperuricemia causes kidney damage by promoting autophagy and NLRP3-mediated inflammation in rats with urate oxidase deficiency - Wu, Mian; Ma, Yiwen; Chen, Xiaoting; Liang, Nan; Qu, Shen; Chen, Haibing (Disease models & mechanisms, 2021)
Epidemiological research has shown that elevated serum urate concentration is a risk factor for the development of kidney disease; however, the mechanisms underlying this process have not yet been elucidated. To examine the role of urate in the kidney, we used Wistar rats to functionally disrupt expression of urate oxidase (UOX) by using the CRISPR/Cas9 system. In comparison to wild-type (WT) rats, serum urate levels spontaneously and persistently increased in UOX-KO rats, without showing a significant decrease in survival rate. Architecture and function of the kidneys in UOX-KO rats were impaired. Injury to the kidney resulted in increased interstitial fibrosis, macrophage infiltration, increased expression of NLRP3 and IL-1β, and activation of multiple cell-signaling pathways associated with autophagy, such as AMPK, p38 MAPK, ERK and JNK pathways. Inhibition of autophagy with the PI3K inhibitor 3-MA abrogated the development of kidney damage and attenuated renal fibrosis, macrophage infiltration, and expression of NLRP3 and IL-1β in injured kidneys. In conclusion, the UOX-KO rat is a great model to study hyperuricemia-related diseases. Hyperuricemia-induced autophagy and NLRP3-dependent inflammation are critically involved in the development of renal damage and, therefore, highlight the inhibition of autophagy and inflammation in search of therapeutic strategies to treat uric acid nephropathy.